2017
DOI: 10.18632/oncotarget.15459
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 4 (KLF4) regulates the miR-183~96~182 cluster under physiologic and pathologic conditions

Abstract: MicroRNAs (miRNAs) are a class of endogenous non-coding small RNAs that post-transcriptionally control the translation and stability of target mRNAs in a sequence-dependent manner. MiRNAs are essential for key cellular processes including proliferation, differentiation, cell death and metabolism, among others. Consequently, alterations of miRNA expression contribute to developmental defects and a myriad of diseases.The expression of miRNAs can be altered by several mechanisms including gene copy number alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…however, studies with greater samples and in different stages to know the role in CRC progression were necessary. In a recent study, miR-10b was found to target Kruppel Like Factor 4 (KLF4), resulting in a classically metastatic and aggressive phenotype (36), but the molecular mechanism in CRC is not known. The zinc finger E-box binding homeobox 1 (ZEB1) protein is the main element in EMT (37).…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…however, studies with greater samples and in different stages to know the role in CRC progression were necessary. In a recent study, miR-10b was found to target Kruppel Like Factor 4 (KLF4), resulting in a classically metastatic and aggressive phenotype (36), but the molecular mechanism in CRC is not known. The zinc finger E-box binding homeobox 1 (ZEB1) protein is the main element in EMT (37).…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…The transcription factor TWIST-1 has also been reported to induce miR-10b, which promotes metastasis by targeting Homeobox D10 (HOXD10), which is associated with the inhibition of cell migration and may reduce E-cadherin expression, resulting in EMT ( 35 ); this mechanism is associated with hypermethylation of the miR-10 promoter in CRC tissues; however, studies with greater samples and in different stages to know the role in CRC progression were necessary. In a recent study, miR-10b was found to target Kruppel Like Factor 4 (KLF4), resulting in a classically metastatic and aggressive phenotype ( 36 ), but the molecular mechanism in CRC is not known.…”
Section: Epithelial–mesenchymal Transitionmentioning
confidence: 99%
“…Patients with depression and animal models of depression show changes in miRNA expression (Dwivedi, 2011 , 2016 ; Chan and Kocerha, 2012 ; Ma et al, 2016 ) as well as the levels of transcription factors, such as KLF11 and R1 (Johnson et al, 2011 ; Harris et al, 2015 ). It has been reported that KLF3 and KLF4 regulate the expression levels of miR-182 (Sachdeva et al, 2015 ; Segura et al, 2017 ), indicating that KLF family of proteins may regulate the expression levels of miRNAs and further modulate the downstream signaling of the pathway. Therefore, it is plausible to hypothesize that KLF11 could regulate the expression of miRNAs in the brain and influence the regulation of MAO-A.…”
Section: Possible Mechanism Of Mao-a Regulation By Mirnasmentioning
confidence: 99%
“…Numerous studies have demonstrated that dysregulation of miRs contributes to the tumorigenesis and progression in many cancer types including NPC and can be associated with prognosis [6][7][8]. As a member of the highly conserved miR-183-96-182 cluster [9], miR-182 is located on human chromosome 7q32.2 [10]. And recent data show that miR-182 may play an oncogenic role in many human cancers, including the breast [11,12], colorectal [13], prostate [14] and bladder cancer [15].…”
Section: Introductionmentioning
confidence: 99%